Outcome Following Decompressive Surgery for Malignant Middle Cerebral Artery Infarction - Nepal, Pankaj Raj; Rijal, Suman (Eastern Green Neurosurgery, 2020)
Background and purpose: When >50% of the brain supplied by middle cerebral artery (MCA) gets infracted they are often termed as malignant MCA infarction. Decompressive hemicraniectomy has became the standard treatment option in carefully selected cases with higher survival benefit (78% Vs 29%) in a pooled analysis of one year follow up; however, there was no promising outcome noted in terms of disability rating. To see the outcome following decompressive hemicraniectomy and lax duroplasty for malignant middle cerebral artery (MCA) infarction this study was pserformed. Materials and Methods: This is a retrospective analytical study, with non-probability consecutive sampling of decompressive hemicraniectomy with lax duroplasty for malignant MCA territory infarction over the last 4 years were collected and Glasgow outcome scale (GOS) at one and six month were measured. The significance was analyzed using chi square or Fisher exact test wherever applicable using SPSS-20. Results: Total 31 cases, with male predominance (74.2%), and mean age of presentation was 51.9 years. Most commonly operated side was on the left (58.1%). Overall favorable outcome at 6 month was 35.5%. When operated for the preoperative GCS of >8, favorable outcome was observed in 30.8% at one month and 76.9% at six months which was statistically significant. Conclusion: Decompressive hemicraniectomy with lax duroplasty has a significant survival benefit. The outcome is significantly better when the preoperative GCS is >8.